Cardiovascular Risk Factors among Patients with Systemic Lupus Erythematosus Presented in a Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Risk factors for cardiovascular disease are particular habits, behaviors, circumstances or conditions that increase a person's risk of developing cardiovascular disease, including lack of exercise, unhealthy eating, smoking, diabetes, age and family history. Cardiovascular risk factors were observed and compared to find out their contribution among patients with SLE.Materials and methods: In this case control study, consecutive patients with SLE attending the Department of Medicine Dhaka Medical College Hospital (DMCH) were studied. The control population was recruited from subjects attending the other departments of the hospital and healthy attendants. The prevalence of classic Framingham cardiovascular risk factors, lipid profile, other metabolic risk factors, lifestyle variables, and demographic characteristics were compared between the 2 groups.Results: 80 SLE patients and 80 age and sex matched controls were studied. Patients with SLE had significantly high BMI and waist circumference (p_0.012 and p_0.001 respectively). Hypertension, diabetes were significantly more common among the SLE patients (31.29% versus 11.25%, p_0.023 and 13.75% versus 3.75, p_0.03). In comparison with control, patients with SLE had no significant difference in mean total cholesterol (193.92±23.65 versus 183.66±11.39, p_0.41) and triglyceride (174.77±60.06 versus 149.15±28.68, p_0.11), but had significantly higher low density lipoprotein (120.77±16.07 versus 108.17±11.68, p_0.00) and lower high-density lipoprotein cholesterol (41.37±4.52 versus 43.51±3.34, p_0.00).  Conclusion: Patients with SLE have a range of detectable and significant cardiovascular risk factors.JCMCTA 2022 ; 33 (1) : 160-165